Trends in mortality due to gastrointestinal diseases attributed to alcohol use in Peru from 2003 to 2016 - Hernández-Vásquez, Akram (2019)
Objective: To assess and identify changes in the temporal trend in mortality from alcohol-attributable gastrointestinal diseases and their disease burden based on years of life lost (YLL) in Peru. Materials and methods: An ecological study of the death records of the Ministry of Health of Peru was conducted from 2003-2016. A gastrointestinal death attributable to alcohol was considered if the basic, intermediate, or final cause of death included ICD-10 codes: K70, K700-4, K709, K292, K852, and K860. Crude and age-adjusted mortality rates were calculated for the general population aged 15 or older and by sex, and YLL. Joinpoint regression analysis was performed to evaluate trends in mortality. Results: There were 11 148 deaths by alcohol-attributable gastrointestinal diseases, being more frequent in males (74.89%), in adults aged 45 years and above (83.67%), living in urban area (69.87%) and the Andes region (60.0%), and in subjects with liver disease (85.98%). Adjusted mortality rates varied from 6.21 (95% CI: 5.78- 6.63) in 2003 to 3.95 (95% CI: 3.67-4.22) in 2016. The trend of mortality decreased in the general population (APC: -6.17, 95% CI: -9.9 to -2.2, p=0.007) during the period 2008-2016. Deaths from the causes studied generated 224 545 YLL. Conclusions: A declining trend was found in gastrointestinal deaths attributable to alcohol in the period 2008-2016. The highest mortality occurred in males, individuals aged 45 years and above, living in urban areas and the Andes region.